Decolonising The Geographical Tradition. Issue 3 (28th March 2019) - Craggs, Ruth
Abstract : The Geographical Tradition played a key role in highlighting geography's imperialism in the 19th and early 20th centuries and prompted a wave of necessary research into the discipline's colonial and racist past. However, both the book itself and the scholarship it subsequently inspired have overlooked the role of geographers from the Global South almost entirely, reinforcing geography's exclusionary traditions. More inclusive disciplinary histories that embrace the contributions of scholars from the post‐colonial world in their contents and reference lists, and that tackle directly not only the history of ideas, but also broader, crucial, questions about academic labour, might be better able to contribute to the challenge of "decolonising" the discipline today.